A continuum damage based approach for cavitation and shear failure of hyperelastic adhesives for finite element applications. Issue 1 (17th December 2018) - Nelson, Alexander; Matzenmiller, Anton
Abstract: Ship‐ and rail‐vehicle building as well as the automotive industry use rubber‐like adhesives for glazing and joining of structural components. These adhesives are suitable to compensate relative motions of adherends due to their ability to withstand large elastic strains. In service, the adhesive layer exhibits distinct amounts of isochoric and volumetric deformations that decisively effect the occurence of two different failure mechanisms. In this contribution, a material model of a rubber‐like adhesive is proposed, which accounts for cavitation and shear fracture. A polynomial strain energy density function is applied to describe the hyperelastic response. The failure is modelled with a continuum damage based approach using an energy based failure function. Computations of a component‐like specimen are performed to validate the model.